Beispiel Nr: 25
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 3x +6y =8\\ 9x +0y = 9 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 3 x +6 y =8\\ II \qquad 9 x +0 y = 9 \\ \text{I nach x auflösen}\\ 3 x +6 y =8 \\ 3 x +6 y =8 \qquad /-6 y\\ 3 x =8 -6 y \qquad /:3 \\ x =2\frac{2}{3} -2 y \\ \text{I in II}\\ 9 (2\frac{2}{3} -2 y ) + 0 y = 9 \\ 24 -18 y +0 y = 9 \qquad / -24 \\ -18 y +0 y = 9 -24 \\ -18 y = -15 \qquad /:\left(-18\right) \\ y = \frac{-15}{-18} \\ y=\frac{5}{6} \\ x =2\frac{2}{3} -2 y \\ x =2\frac{2}{3} -2 \cdot \frac{5}{6} \\ x=1 \\ L=\{1/\frac{5}{6}\} \end{array} & \begin{array}{l} I \qquad 3 x +6 y =8\\ II \qquad 9 x +0 y = 9 \\ \text{I nach y auflösen}\\ 3 x +6 y =8 \\ 3 x +6 y =8 \qquad /-3 x\\ 6 y =8 -3x \qquad /:6 \\ y =1\frac{1}{3} -\frac{1}{2}x \\ \text{I in II}\\ 9x + 0(1\frac{1}{3} -\frac{1}{2} x ) = 9 \\ 0 -0 x +0 x = 9 \qquad / -0 \\ -0 x +0 x = 9 -0 \\ 9 x = 9 \qquad /:9 \\ x = \frac{9}{9} \\ x=1 \\ y =1\frac{1}{3} -\frac{1}{2} x \\ y =1\frac{1}{3} -\frac{1}{2} \cdot 1 \\ y=\frac{5}{6} \\ L=\{1/\frac{5}{6}\} \end{array} \end{array} $